Geopathic Stress, Perceived Stress, and Spirituality of Female Prison Inmates: Initial Calculation - Convocar, Jeremias; Mamon, Michelle; Clarin, Heidi (JPAIR Institutional Research, 2019)
Incarceration stress among female prison inmates cannot be avoided, but it has to be coped with. This descriptive-correlational study determined the level and extent of the relationship among perceived stress (PS), geopathic stress (GS), and spirituality of 116 purposively and conveniently selected female prison inmates of certain city Rehabilitation Center in the Philippines, during the third quarter of the Fiscal year 2019. The study utilized the adopted Cohen and Williamson (2008) PS Scale, the Spirituality Scale from Hernandez (2011), and Convocar (2014) GS instrument. Statistics employed were Percentages, Means, Standard Deviation, Mann Whitney, and Kruskal Wallis test set at .05 alpha. The findings revealed that the female inmates had a fair level of PS and a high level of spirituality regardless of their age, educational attainment, length of incarceration, and status of the case, and 27 percent were affected by GS. They differed significantly in PS when grouped according to their length of incarceration, the status of a case, and level of GS, and differed significantly in spirituality when grouped according to their age. A negative and significant relationship between the level of PS and spirituality; and a significant positive relationship between the level of GS and PS. Hence, GS and spirituality have to be considered in managing stress among female inmates.